The Effect of Flashcard Media On 5th Grade Students Narrative Essay Writing Skill At UPT SDN Unggulan Bontomanai - Nurhidayah Tahir; Bhakti Prima Findiga Hermuttaqien; Patta Bundu (International Journal of Elementary School Teacher, 2022)
This research conducted of the problems found in elementary school related to writing skills, there are still some students who have difficulty in writing narrative essays. The purpose of this research is to know the description of flashcard media implementation, to know the description of students narrative essay writing skills, and to determine the effect of using flashcard media on narrative essay writing skills of fifth grade elementary school students of UPT SDN Unggulan Bontomanai. The type of research conducted in this research is quantitative experimental with a pretest-posttest control group design, with pretest, treatment, and posttest stages. . The population and sample in this study were fifth grade students of UPT SDN Unggulan Bontomanai, Bontomarannu District, Gowa Regency with a total of 54 students and determined by simple random sampling technique with a sample of 48 students. The data were using the writing skills test, observation sheets and documentation. Data were analyzed using descriptive and inferential analysis. The results of the descriptive analysis showed that the use ofmedia flashcard at the first meeting was sufficient with a percentage of 64% and at the second meeting it went very well with a percentage of 89%. The improvement of students' narrative writing skills in the experimental group was 42% and the control group was 4%. The results of inferential analysis used independent sample t-test showed a probability value of 0.00 < significance level of 0.05 and T count of 5.675 > Ttable of 2.012. So it can be concluded that there is a effect on the use of flashcard media on the narrative essay writing skills of the fifth grade students of UPT SDN Unggulan Bontomanai, Bontomarannu District, Gowa Regency.